Self-Transcendence in Transpersonal Psychology: A Critical Review from the Perspective of the Islamic Worldview - Jarman Arroisi; Husain Zahrul Muhsinin; Ahmad Rizqi Fadlilah (Research Synergy Foundation, 2024)
Transpersonal psychology offers a perspective that emphasizes the spiritual aspects of human experiences and consciousness, summarized in a concept that represents human's spiritual consciousness, self-transcendence. Unfortunately, its formalized concept, along with its spiritual aspects, showed the necessity for further inquiry, especially from the Islamic worldview. This research aimed to critically review the concept of self-transcendence in transpersonal psychology from the perspective of the Islamic worldview. This research was done by applying the library research method, collecting data from the works of Viktor Frankl and Abraham Maslow, who are prominent figures in the related topic, in addition to the works of various scholars about transpersonal psychology. The researcher used an analytical method to analyze it. After completing this research, the researcher found out that 1) the concept of self-transcendence formulized in the framework of existentialism implied to be inevitably anthropocentric, which needed to be criticized by replacing it with the Islamic theocentric framework; 2) the misconception of its spiritual aspect provides experiences that cannot represent genuine and authentic spirituality, whether in a state of inclusive spirituality or a form of spiritual pluralism; 3) self-transcendence from Islamic perspective required not only horizontal connection with nature but also vertical transpersonal with God so that it can fulfil one's inherent nature and consequently live a meaningful life in obedience to his God. Based on these findings, the researcher concluded that self-transcendence in transpersonal psychology was infected with the Western paradigm. Therefore, it should be cured by applying the Islamic worldview to gain proper relation between self and God and other creatures.